1991
DOI: 10.1002/gps.930061007
|View full text |Cite
|
Sign up to set email alerts
|

The domus philosophy: A comparative evaluation of a new approach to residential care for the demented elderly

Abstract: SUMMARYThis study reports a cross-sectional comparison between three continuing care facilities for severely disturbed elderly demented people: two mental hospital psychogeriatric wards and a unit run according to the domus philosophy of care. The domus was characterized by greater expectations for residents' functioning, policy choice, resident control and availability of social and recreational activities. The level of staffing was higher on the domus than on the two wards. The residents on the three setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 10 publications
(9 reference statements)
2
38
0
Order By: Relevance
“…Strict nursing tasks, such as taking blood pressure or giving enemas, are far more likely to This study, while focusing on principal dierences between EMI wards and the alternative community facilities, has also drawn attention to dierence between community facilities managed by the NHS and those managed by Social Services. It was observed that the two facilities run by Social Services provided no on-site nursing or medical servicesÐa practice which is common in many other`domus' type facilities in the UK (Lindsey et al, 1991;Dean et al, 1993). Apparently, these care environments are driven by a concept which gives precedence to the psychological and emotional well-being of the residents over the physical aspects of care.…”
Section: Discussionmentioning
confidence: 96%
“…Strict nursing tasks, such as taking blood pressure or giving enemas, are far more likely to This study, while focusing on principal dierences between EMI wards and the alternative community facilities, has also drawn attention to dierence between community facilities managed by the NHS and those managed by Social Services. It was observed that the two facilities run by Social Services provided no on-site nursing or medical servicesÐa practice which is common in many other`domus' type facilities in the UK (Lindsey et al, 1991;Dean et al, 1993). Apparently, these care environments are driven by a concept which gives precedence to the psychological and emotional well-being of the residents over the physical aspects of care.…”
Section: Discussionmentioning
confidence: 96%
“…Many highlighted assumptions are recognized in the GL program in e.g. the British Domuses [16] and the French Cantous [42]. In these settings, the intention is however to care for the patient throughout the progress of the de menting disease.…”
Section: Discussionmentioning
confidence: 99%
“…To a great extent, this criticism concerns 'the institutional maintenance', whereby procedures and rou tines become geared to the needs of the institution rather than to the needs of the resident [16], The heterogeneity of patients brought together may also counteract the restitu tion of the patient as a social individual [17][18][19], In insti tutional settings, the hospital routines and equipment are usually developed to meet the needs of somatic medical care. In many aspects, the main characteristics of Goffman's [20] total institutions are still valid.…”
Section: A Theoretical Framementioning
confidence: 99%
“…However, these pressures may arguably increase the risk to older people with dementia of less personcentred care, as well as that of excess relocation morbidity and mortality. These risks helped shape the 'Domus' model of care for people with dementia and behavioural problems in South London [1], with respite and day-care proscribed, and emphasizing a 'home for life' principle. Quite apart from ethical concerns, the latter was predicated on the fear that moving someone with dementia to a less intensive form of care when behavioural problems had settled might well produce a resurgence of these problems -as might even planning such a move.…”
Section: Introductionmentioning
confidence: 99%
“…This model is widespread in the UK, and can be considered as a variant of the UK Government's preferred policy of 'intermediate care' [2], but has not been evaluated. The less common Domus model has been evaluated in comparison with traditional long-stay wards and similar units [1,3,4]. We decided to compare the outcome for newly admitted residents to each model of care with the aim of quantifying any excess behavioural decline in those admitted to the MPNHs with the intention of ultimate placement elsewhere ('intermediate care', IC group), over that in those admitted to the Domus or MPNH with the intention that it was to be their home for the rest of their life ('HFL' group).…”
Section: Introductionmentioning
confidence: 99%